2021
DOI: 10.1186/s12889-021-11694-9
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional associations between sedentary time and sleep duration among 12- to 14-year-old adolescents

Abstract: Background The aim of this study was to investigate bidirectional associations between (prolonged) sitting time and sleep duration in 12- to 14-year-old adolescents using a between-subjects and within-subjects analyses approach. Methods Observational data were used from 108 adolescents (53% girls; mean age 12.9 (SD 0.7) years) from six schools in Flanders, Belgium. The Axivity AX3 triaxial accelerometer, worn on the thigh, was used to assess daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, fewer studies have revealed that prolonged sedentary time is an emerging influential factor related to poor sleep quality [ 15 ]. Meanwhile, some studies have found that the duration of subsequent nighttime sleep was shorter when daytime sedentary time increased [ 16 ], and interventions that focus on regularly interrupting sedentary time could improve the sleep duration of young people [ 17 ]. However, some studies using accelerometers have reported that the average daily sedentary time ranged from 8.23 to 13.03 h per day [ 18 , 19 , 20 , 21 , 22 ], while another study found that the sedentary time of college students is increasing [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, fewer studies have revealed that prolonged sedentary time is an emerging influential factor related to poor sleep quality [ 15 ]. Meanwhile, some studies have found that the duration of subsequent nighttime sleep was shorter when daytime sedentary time increased [ 16 ], and interventions that focus on regularly interrupting sedentary time could improve the sleep duration of young people [ 17 ]. However, some studies using accelerometers have reported that the average daily sedentary time ranged from 8.23 to 13.03 h per day [ 18 , 19 , 20 , 21 , 22 ], while another study found that the sedentary time of college students is increasing [ 23 ].…”
Section: Introductionmentioning
confidence: 99%